The Review On The Role Of Social Companion In The Implementation Of Family Hope Program (PKH) In Darul Falah District, East Aceh During The Covid-19 Pandemic - Muhammad Bin Abubakar; Amran Amran; Mulyadi Mulyadi (Malikussaleh Social and Political Reviews, 2022)
AbstractThis research examines the implementation of the PKH Program, an overview of the role of PKH Social Assistants during the Covid-19 Pandemic. The research location is in Darul Falah District of East Aceh Regency. The research objective was to describe and analyze the implementation of the PKH Program in Darul Falah District of East Aceh Regency during the Covid-19 Pandemic and to describe and analyze the role of PKH Social Assistants in the PKH Program assisted areas during the Covid-19 Pandemic. In conducting this research the writer used a descriptive research method with a qualitative approach.  The results of the study found that the role of PKH Social Assistants in Darul Falah District of East Aceh Regency in 2020 is a description of the implementation of the PKH Program in Darul Falah District of East Aceh Regency during the Covid-19 Pandemic. This activity is a daily activity carried out by PKH Social Assistants in order to cut off the spread of the Corona Virus in Darul Falah District of East Aceh Regency. In order to break the chain of spreading the Corona Virus in the community, PKH Social Assistants in Darul Falah District of East Aceh Regency is active in various Covid-19 volunteer activities in eleven villages in the Darul Falah District of East Aceh Regency. Various activities carried out by PKH Social Assistants in Darul Falah District of East Aceh Regency in the field with KPM during the Covid-19 pandemic were carried out by following health protocols. Keywords: PKH Program, Role of Social Companion, Covid-19